Managing Organizational Change in Pakistan: Insights from the Work of Kurt Lewin. - Haroon Bakaria; Ahmed Imran Hunjra; Muhammad Tahir Masood (UW Journal of Management Sciences, 2022)
Purpose: Main objective of this paper is to review the literature on the theories of Kurt Lewin with special focus on three-step model and discuss relevance of this model for Pakistani organizations Background: Kurt Lewin, a prominent social psychologist has been regarded as father of planned change. His seminal work in planned approach to change management and resolution of social conflicts has received considerable attention of academics and practitioners alike. Design/ methodology/Approach: this study used deductive approach to draw conclusions from available literature. This study begins by searching relevant studies and extract relevant information. Findings: this study has found that theories of Kurt Lewin especially three-step model is still relevant to managing organizational change in Pakistan. This study also suggests a model which may be used by leaders as a tool to implement planned change in Pakistan. Research limitations/implications/ recommendations: this study has not used any empirical data therefore future research may continue to test empirical validity of Lewin’s three-step model